Exploring Pain Management Strategies and Their Influence on Patient Satisfaction After Abdominal Surgeries: A Qualitative Inquiry in Federal Teaching Hospitals, South-West Nigeria - Dada, Rotimi Williams; Nwaomah, Esemota; Jummai, Wennie; Bello, Qazim; Abiodun, Titilayo; Opaleye, Temitope; Ogunleye, Adebisi; Omitogun, Olusola; Orunmuyiwa, Grace; Dada, Ayokunnumi (Journal of Applied Nursing and Health, 2025)
Background: Patient satisfaction is a key indicator of healthcare quality, particularly about postoperative pain management. Abdominal surgery remains one of the most common major procedures performed in teaching hospitals across Nigeria. However, previous studies have reported prolonged hospital stays, delayed recovery, and increased postoperative complications due to inadequate pain control. Despite the high volume of abdominal surgeries, there is limited evidence on the most effective pain management strategies to improve patient satisfaction. Notably, many patients in federal teaching hospitals in South-West Nigeria continue to express dissatisfaction following surgery. This study examined pain management strategies that enhance patient satisfaction following abdominal surgery in selected federal teaching hospitals in South-Western Nigeria. Methods: A qualitative research design was employed. Twelve patients undergoing postoperative abdominal surgery were purposively selected until data saturation was achieved. Semi-structured interviews were conducted using an interview guide, and the data were analyzed thematically. Results: Six major themes emerged from the analysis: (1) patients’ experiences of abdominal surgical pain, (2) satisfaction with current pain management methods, (3) factors promoting coping mechanisms, (4) fear of drug-related adverse effects, (5) strategies adopted for pain management, and (6) patients’ suggestions for improving pain control. Conclusion: The study concluded that the use of a combination of pain management strategies significantly enhanced patient satisfaction following abdominal surgery. It is recommended that hospital management implement policies that support the use of multimodal pain management approaches by nurses, with a focus on personalized and compassionate care, to optimize postoperative outcomes and patient satisfaction.